Overlooked : South Korea’s Naval Shipbuilding - Bitzinger, Richard A. (2019)
South Korea’s sea trials of new indigenous submarine demonstrate that the country’s naval shipbuilding industry is entering a new phase of proficiency. This will mean a more capable blue-water South Korean navy, as well as promising to make Korea a major player in the global arms market.